Compactação do solo e adubação com cinza vegetal na cultura do cártamo em solo do cerrado mato-grossense - Santos, Tulio Martinez (2018)
The increase of mechanized areas favors the soil compaction in subsurface, in this sense, the addition of agricultural residues to the soil with the purpose of improving the chemical and physical qualities of the soil. Thus, the objective of this study was to evaluate the effect of soil bulk density levels associated with wood ash doses on safflower crop performance. The experiment was conducted in a greenhouse under a randomized block design with five levels of soil compaction (bulk densities: 1.0, 1.2, 1.4, 1.6 and 1.8 Mg m-3 ) and fertilized with five doses of wood ash (0, 8, 16, 24, 32 g dm-3 ). The applications of the doses of wood ash occurred immediately after the collection of the soil according to the respective treatments. Each experimental unit was formed from a PVC (polyvinyl chloride) vessel with three isometric rings attached by silver tape. The vessels had 200 mm of internal diameter and 300 mm of height, totaling 9.4 dm³ of soil. The layer 0,1-0,2m was compacted using the hydraulic press (P15ST, BOVENAU) according to the treatments, while the upper and lower layers were filled with soil equivalent to 1.0 Mg m-3 density. To meet the nutritional needs of the plant nitrogen fertilization with 150 mg dm-3 nitrogen was divided in three biweekly applications from the 15th day after emergence 40, 55 and 55 mg dm-3 at 15, 30 and 45 days after emergence respectively. The evaluations were performed at 15, 30, 45, 60, 75 days after the emergency. The vegetative evaluations with the 0 g dm-3 treatment were performed only 15 days after emergence, since from that date, the plants died due to the low base saturation of the soil. The results were submitted to analysis of variance and significance was verified to the regression analysis using SISVAR software with significance of 5%.For the majority of the vegetative variables, there was a significant interaction isolated for the doses of wood ash and levels of bulk density, being, doses close to 24 g dm-3 of the residue provided a more vigorous vegetative development, as far as the levels of bulk density, these showed a linear decreasing response, except for the SPAD index, which presented an inverse result. However, for root development, the dose of plant ash was observed as higher yields of dry mass and root volume at fertilization close to 24g dm-3. To the levels of soil density, it was observed that the plants adapted to the majority of the linear model of regression decreasing with the increase of soil density, with the advantage in the superior qualifications, that are adjusted to the quadratic model of regression. The levels of density of soil and compositions of culture may be evaluated. The addition of vegetable ash is positive for the development of safflower culture at a dose of 24 g dm3 . Increased levels of soil density, detrimental to the vegetative and root development of safflower